Evaluating higher taxa as surrogates of harvestmen biodiversity (Arachnida: Opiliones) along a latitudinal gradient in the Atlantic Forest - de Andrade, Alessandra Rodrigues Santos; de Azevedo Koch, Elmo Borges; do Amaral Nogueira, André [UNESP]; Pinto-da-Rocha, Ricardo; Bragagnolo, Cibele; Lorenzo, Everton; DaSilva, Márcio Bernardino; Delabie, Jacques Hubert Charles (Wiley, 2023)
Habitat loss and fragmentation have highlighted the importance of monitoring remaining habitats. For megadiverse groups such as arthropods, of which many species are still being discovered, the use of higher taxonomic levels as substitutes for diversity may be a useful tool. The aim of this study was to evaluate the use of substitute taxonomic resolutions to assess the richness and composition of Laniatores harvestmen (Arachnida: Opiliones). The five resolutions selected were as follows: genus, family, subfamily, indicator taxa and intermediate resolution (combination of genus and species identification levels). In addition, we evaluated whether the diversity substitutes provide good estimates of latitudinal gradients. Nineteen Atlantic Forest sites located along a latitudinal gradient in northeastern Brazil were sampled. We recorded a total of 88 harvestmen species/morpho-species, distributed in 7 families, 15 subfamilies and 36 genera. Genus and intermediate resolution were excellent substitutes for harvestmen species richness. The efficiency differed according to the substitute resolution used. Four resolutions were adequate to replace the harvestmen composition: genus, intermediate resolution, indicator taxa, and subfamily. The number of harvestmen species recorded was significantly different between Seasonal Semideciduous Forest and Costal Atlantic Rainforest. The same relationship was also observed the same relationship was observed when we consider genus and intermediate resolution. Our results suggest the use of genus as a substitute for richness and composition of harvestmen for reducing monitoring costs and providing evaluation in a shorter time and a more practical way.
Keywords: biodiversity assessment; biodiversity surrogates; indicator taxa; intermediate resolution; species richness